Pengembangan Platform E-Learning Berbasis Google Sites sebagai Media Pembelajaran Bahasa Arab: Model dan Implementasi - Nurul Aini Latifah, Siti; Hajar Nugroho, Muhammad (Kartika: Jurnal Studi Keislaman, 2025)
This research aims to develop a Google Sites-based e-learning platform to support Arabic language learning at MA Al Abror Sukosewu. The development of this platform seeks to address the limitations of conventional teaching methods, such as lectures and question-and-answer sessions, frequently applied at the school, and aims to encourage students to be proactive and accustomed to using computers. In this study, the researcher employed Research and Development (R&D) using the ADDIE development model. Validation results from experts indicated that this platform is feasible to use. Trials conducted on 12th-grade social science students at MA Al Abror Sukosewu also showed a significant improvement in learning outcomes, with an average post-test score of 87.22 compared to a pre-test score of 15.00. This e-learning platform is expected to serve as an innovative solution to enhance the quality of Arabic language learning at MA Al Abror Sukosewu and encourage students to be more active and independent in the learning process.